Direct Visualization of Actin Filaments and Actin-Binding Proteins in Neuronal Cells - Minkyo Jung; Doory Kim; Ji Young Mun (Frontiers in Cell and Developmental Biology, 2020)
Actin networks and actin-binding proteins (ABPs) are most abundant in the cytoskeleton of neurons. The function of ABPs in neurons is nucleation of actin polymerization, polymerization or depolymerization regulation, bundling of actin through crosslinking or stabilization, cargo movement along actin filaments, and anchoring of actin to other cellular components. In axons, ABP–actin interaction forms a dynamic, deep actin network, which regulates axon extension, guidance, axon branches, and synaptic structures. In dendrites, actin and ABPs are related to filopodia attenuation, spine formation, and synapse plasticity. ABP phosphorylation or mutation changes ABP–actin binding, which regulates axon or dendritic plasticity. In addition, hyperactive ABPs might also be expressed as aggregates of abnormal proteins in neurodegeneration. Those changes cause many neurological disorders. Here, we will review direct visualization of ABP and actin using various electron microscopy (EM) techniques, super resolution microscopy (SRM), and correlative light and electron microscopy (CLEM) with discussion of important ABPs in neuron.